Religious Education at Preschool. Main Assumptions and Kindergarten Teachers’ Opinions - Elżbieta Osewska (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The historical, political, social and cultural issues of the past have strongly impacted upon the current Religious Education at preschools in Poland. In the beginning of socio-political transformation of Poland the confessional nature of Religious Education was one of the demands presented not only by the Church, but also by society. Today, even the presence of Religious Education is discussed. In order to understand better the arguments supporting Religious Education at preschools in Poland, this article will provide kindergarten teachers’ opinions on the basis of a research survey, which was conducted among preschool teachers from Malopolska and Silesia region in April and May 2018.